ANALISIS PENDAPATAN USAHA KERAMABA JARING APUNG (KJA) DI TELUK AMBON DALAM - Pattimukay, Kesya; Pical, Venda Jolanda (PAPALELE (Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan), 2025)
Floating net cages (KJA) are one method of fish farming that is increasingly popular in various coastal areas of Indonesia, including in Ambon City. Economically, KJA plays an important role in increasing the income of fishermen. More stable and controlled fish production through KJA allows fishermen to earn a more certain income compared to traditional fishing. The purpose of this study was conducted to see how many per cent of the increase in income that occurred in the KJA business owner with a job before doing KJA business in Teluk Ambon Dalam. Primary data collection was carried out by interview based on a questionnaire to 9 respondents selected by purposive sampling method according to the criteria that the respondent is an active KJA business owner in Ambon Bay. With the data analysis method using excel application for income, the results showed a significant increase in income of 76% for KJA business owners in Teluk Ambon Dalam compared to their previous jobs. Thus KJA is also a new employment opportunity, both directly in KJA operations and in supporting sectors such as fish processing and marketing and has good prospects in the future